Supervision Management in Early Childhood Education: A Case Study of Learning Quality Improvement in Bandung - Nana Herdiana Abdurrahman; Dani Wardani; Paojan Zam’an; Mohamad Heri Hadian; Reny Jabar; Neni Utami Adiningsih (Jurnal Ilmiah Profesi Pendidikan, 2025)
Supervision management plays a pivotal role in enhancing the quality of education, particularly in early childhood settings. This study investigates the application of supervision management at TK At-Taqwa, Bandung, to address challenges such as monotonous teaching methods, limited professional development opportunities, and ineffective classroom management. Employing a qualitative descriptive approach, data were gathered through in-depth interviews, participatory observations, and document analysis involving principals, teachers, and supervisors. The findings reveal that effective supervision management consists of systematic planning, collaborative execution, and constructive feedback. These practices resulted in significant improvements, including enhanced teacher competence, the adoption of innovative teaching methods, and optimized classroom management. Despite challenges such as limited resources and resistance to change among educators, strong leadership and teacher collaboration emerged as critical enablers of success. This research contributes to the body of knowledge by providing a practical model for implementing supervision management in early childhood education institutions. It underscores the importance of structured supervision practices in fostering professional development and delivering holistic improvements in learning quality, offering valuable insights for educators and policymakers aiming to enhance early education standards.